Hypermodern aspects in the short story “O importado vermelho de Noé”, by André Sant’anna - Moura da Silva, Paulo Ricardo (2018)
The objective of this article is to critically discuss the tale “O importado vermelho de Noé”, by the writer André Sant’Anna (2007), present in the book Sexo e amizade, from the perspective of Gilles Lipovetsky’s reflections (2004) on the fundamental aspects which constitute the hypermodernity. We focus on our critical reading of the possible dialogues between André Sant’Anna’s tale and the discussions of Gilles Lipovetskyto bring them closer to verify certain converging aspects between these two discourses, such as consumption, velocity, as well as the resignifications in the relations that hypermodern individuals establish with time.